Collaborative Writing: Strengths and Weaknesses to Teach EFL Students and Its Relation to Students’ Self-Esteem in Writing - Zahrotun Hanifah (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
As the objectives of learning English is always changing time to time, the way of teaching English should be adjusted to the changeable learning objectives. Recently, the idea of working collaboratively has given so much influence towards the development of methodology in language teaching and learning. Collaborative writing has been broadly discussed as one of the best methods to teach writing. This study aims to describe the strengths and weaknesses of collaborative writing to teach writing for EFL students and how it links to their self-esteem. The method of this study is qualitative while the design of this study is case study. The data collecting techniques were observation, interview, and document analysis. The results showed that collaborative writing gives opportunity for EFL students to experience the better writing process where students can share and discuss in exploring ideas, developing ideas, expressing ideas, and evaluating the writing product. In terms of their self-esteem, students with low self-esteem were discouraged and tended to depend their writing work on the higher level students. In contrast, students with high self-esteem were encouraged in writing when they were responsible to lead their friends during writing process.